2014
DOI: 10.1002/pri.1610
|View full text |Cite
|
Sign up to set email alerts
|

Are Established Methods of Physiotherapeutic Management for Long‐term Neurological Conditions Applicable to ‘Orphan’ Conditions such as Syringomyelia?

Abstract: Syringomyelia patients report physiotherapy to provide benefits for symptom management and quality of life. Such findings suggest that established rehabilitation techniques in more common conditions may be transferable to those less prevalent. Uptake of physiotherapy was limited, seemingly because of inadequate information, knowledge and resources. To address these deficiencies, further studies should be planned investigating the effectiveness of physiotherapy modalities, such as hydrotherapy, in parallel or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 45 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…All study samples were independent, and studies were of different designs. Three of the identified studies were retrospective cohort studies using clinical data, interviews, and questionnaires ( 15 , 19 , 20 ), while 4 were case reports ( 21 – 24 ). Sample sizes varied from a single case (the 4 case studies) to 5, 14, and 67 patients who were managed conservatively in the 3 cohort studies, respectively, which in addition also reported on surgically managed patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All study samples were independent, and studies were of different designs. Three of the identified studies were retrospective cohort studies using clinical data, interviews, and questionnaires ( 15 , 19 , 20 ), while 4 were case reports ( 21 – 24 ). Sample sizes varied from a single case (the 4 case studies) to 5, 14, and 67 patients who were managed conservatively in the 3 cohort studies, respectively, which in addition also reported on surgically managed patients.…”
Section: Resultsmentioning
confidence: 99%
“…Patients’ age ranged from 18 to 80 years, and, for the 4 studies reporting on this ( 21 – 24 ), syrinx locations included all parts of the medulla, often spreading over several levels. While the 2 biggest studies had mixed populations in relation to underlying pathology (both PSS and others) ( 19 , 20 ), the study by Ronen et al ( 15 ) described 5 cases that all had PSS. Among the 4 single case studies, 1 described PSS related to a specific condition (Hirayama disease) ( 21 ), and 3 referred to patients with PSS after trauma ( 22 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before after intervention, focus groups, interviews 55 Curtis et al, (2015), Canada 49 To conduct a modified yoga program for individuals with SCI, in terms of both participant experiences and program satisfaction.…”
Section: Mixed Methodsmentioning
confidence: 99%
“…Of the 31 studies that reported the type of SCI, 20 studies had participants with both traumatic and non-traumatic injuries, 44,47,49,51,53,[56][57][58][59]61,[63][64][65]67,69,73,77,79,80,85 10 studies had participants with only traumatic injuries 45,62,66,70,72,[74][75][76]81,84 and 1 included participants with only non-traumatic injuries. 55 None of the studies reported if the participants were diagnosed with other comorbidities.…”
Section: United States 82mentioning
confidence: 99%